Mentoring early career researchers - Mercer, Theresa G.; Margineanu, Michael-Bogdan (Springer, 2025)
The Curious Future Insight Conference is a platform that brings together scientists from around the world every 2–4 years to discuss the latest advances and innovations in science and technology with the aim of ‘uniting through science for a better tomorrow’. Over the 2-day gathering, a number of themes are covered relating to Energy, Healthy Lives, the Human Mind, Life Reimagined, Materials & Solutions, Nutrition and Vibrant Digital. In the 2024 conference, the importance of mentoring and supporting Early Career Researchers within the wider science ecosystem was a prominent feature of a panel session hosted by AAAS/Science and moderated by Dr. Rachel Bernstein of Science, deputy news editor focusing on careers and community. In this panel session that also included Dr. Senka Holzer, Medical University of Graz and Professor Ulrike Fasbender, University of Hohenheim in Germany, we explored the importance of the mentor/mentee relationship from a scientific and professional perspective, how the relationship can help individuals in navigating challenges within a science career and strategies and approaches for fostering the relationship. This chapter will address some of these main themes around mentoring relationships, bringing in our insights and personal perspectives.
Keywords: Science; 4701 Communication and Media Studies; 32 Biomedical and Clinical Sciences; 47 Language, Communication and Culture; mentoring; challenges; support; mentor/mentee relationship; responsibilities; reverse mentoring; research advisor